Empowerment of Indonesian MSME Business Performance: An Empirical Analysis of Knowledge Sharing and Innovation - Wahyuda, Okta; A. Syukur, M- Hanafi; Bagus Purmono, Bintoro; Pebrianti, Wenny; Setiawan, Harry (International Journal of Scientific Research and Management (IJSRM), 2023)
AbstractThe wheel of a country's economy is driven by the growth of Micro, Small, and Medium Enterprises (MSMEs). Structural socio-economic changes from MSME business activities can improve people's living standards, such as absorbing jobs, fostering a sustainable business climate, and equal distribution of people's income. Along with the increasing number of MSMEs, business actors are required to strengthen business performance through innovation orientation in the products they produce. Knowledge sharing is one of the competitive advantages built by the company so that MSMEs are guided in carrying out business activities. Acquiring knowledge and skills through collaboration is an effective and efficient effort to innovate in the business environment. This study examines knowledge sharing and product innovation in MSME performance management. The study used a quantitative method of 225 respondents based on purposive sampling criteria. The implementation of Structural Equation Modelling (SEM) with the AMOS 24 statistical tool was applied to test the feasibility of the data and research hypotheses.Keywords: Knowledge Sharing; Product Innovation; Business Performance